Aportes a los nuevos estudios literarios sobre el tradicionista: Con motivo de los veinte años del Instituto Ricardo Palma - Pantigoso Pecero, Manuel (2018)
In the introduction appears some axis ideas emerged from the hermeneutic work of the Ricardo Palma Institute. Some of the main contributions of Palma to the contemporary literary studies are examined: the new concept of history; his relation with poetic fiction and the concealment of the own life; the conciliatory spirit as “truth of the imagination”; the impeller of the literary criticism; his condition as forefather of Modernism; his affinity with Garcilaso in the discovery of Peru.